Kepemimpinan Partisipatif,Delegasi,Dan Pemberian Kewenangan - Teguh Pamungkas; Jamrizal Jamrizal; Kasful Anwar Us (Lembaga Pengembangan Kinerja Dosen, 2024)
This paper discusses three important aspects of modern organizational leadership: participative leadership, delegation, and granting authority. Participative leadership provides space for active participation of team members in decision making, while delegation allows leaders to share responsibilities. Granting authority is an important step to empower team members. The combination of these three elements can create a productive and empowering work environment